CONCEPTUAL FORMATION OF STUDENTS’ PROFESSIONAL-PEDAGOGICAL CULTURE IN THE SYSTEM OF SPECIAL PHYSICAL TRAINING EDUCATION - Ivanii, Igor (Continuing Professional Education: Theory and Practice, 2019)
The actuality of the investigation of the problem of formation of professional-pedagogical culture of future physical training and sport specialists are determined by modern tendencies of physical culture development and the need to prepare competent personnel, who is capable to realise effectively special social tasks of cognition, transmission and creation of culture, and to prepare new generations to solve global humanistic, cultorological and physical culture problems. The aim of the article is to work out the conceptual bases of formation of professional-pedagogical culture of student’s personality in the system of special physical culture education. The results of educational curriculum content analysis, and analysis of curriculum of disciplines of corresponding specialisations has enabled us to work out the conception of students’ professional-pedagogical culture, which is the system of scientific views and interpretations, theoretic and methodological approaches, basic ideas, principles and pedagogical regularities and tendencies, which determine the process of formation of students professional-pedagogical culture in the system of his professional training. Professional-pedagogical culture is an element of pedagogical system, integrated mass of students’ personality, that is realised in measures and methods of his creative self-realisation in manifold types of sport activities and communication, which is directed to the mastering and creating professional-pedagogical values and person’s abilities, generalized indicator of professional competence and the aim of professional self-improvement.